Land Cover Change and Ecosystem Services Trade-Off in the Tiworo Watershed: Implications for Forest Conservation and Watershed Management - Kasim, Safril; Hasddin; Fariki, La; Agarwal, Abhishek (Jurnal Sylva Lestari, 2026)
This study evaluates the spatio-temporal dynamics of land-cover change and their implications for the sustainability of ecosystem services in the Tiworo Watershed, Southeast Sulawesi, Indonesia, using an integrated ecological–economic framework. The analysis combined land cover datasets from 2014, 2019, and 2024 with sectoral gross regional domestic product (GRDP) data for agriculture, forestry, and fisheries, and applied the Tapio decoupling model to assess the relationship between economic growth and ecological pressure. Results revealed substantial expansion of built-up areas, plantations, and aquaculture ponds, primarily at the expense of mangrove forests and wetlands. Mangrove cover declined from 431.61 ha in 2014 to 306.77 ha in 2024, indicating increasing pressure on coastal ecosystems. Despite these changes, secondary dryland agriculture and forest areas remained relatively stable, suggesting partial resilience of the watershed landscape. Economically, the agriculture, forestry, and fisheries sector consistently contributed 38–41% of regional GRDP, confirming its strategic importance to local livelihoods and regional development. Decoupling analysis demonstrated absolute decoupling during 2014–2019 and 2014–2024, while relative decoupling occurred during 2019–2024, indicating that economic growth increasingly outpaced ecological degradation. However, localized ecosystem degradation, particularly in mangrove areas, remains a critical concern. These findings highlight that the Tiworo Watershed is transitioning toward more resource-efficient development, although long-term sustainability depends on adaptive watershed governance, stricter protection of vulnerable ecosystems, improved land-use planning, and strengthened community-based forest management. The study provides empirical evidence supporting the application of decoupling analysis at the tropical micro-watershed scale and contributes to the development of integrated forest and watershed management strategies in data-limited regions. Keywords: ecosystem services, forest management, land cover change, Tapio decoupling, Tiworo Watershed